PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 2 KELAYANG - ', Kasmila; ', Gimin; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to find out how much influence of learning motivation on the learning outcomes of economic subjects class X SMA Negeri 2 kelayang. The population of this study is all students of class X SMA Negeri 2 Kelayang with the number 90 with the sample that is 48 people, the sample is taken using proportional random sampling technique. The data used are primary data and secondary data with data collection methods using questionnaires and documentation. Data analysis technique used is Descriptive Analysis and Simple Linear Regression Analysis processed through SPSS 17 program. For Windows student motivation in this research belong to high category that is 37,5% while student learning result is classified into good category once 62,5%. The results of this study indicate that the motivation effect on the results of learning subjects economy class X SMA Negeri 2 Kelayang. This means that the higher the students' learning motivation will also improve student learning outcomes. Thus, to improve student learning outcomes, the support of the teacher and the student's environment is motivation.Keywords: Motivation learning, learning outcomes